Compendium of Evaluation Studies Conducted by Programme Evaluation Organisation (1952-70) Volume - I - Planning Commission (Planning Commission, 1997)
Evaluation is an integral part of planning process and an indispensable input for policy formulation and implementation. An efficient evaluation system can play an important role in improving the process of implementation of programmes, schemes and projects, and more importantly ensuring that the benefits of development projects reach the intended beneficiaries. Therefore, it is essential to strengthen the process of evaluation of development projects.
Programme Evaluation Organisation, Planning Commission, Govt. of India